Sunday

April 20, 2014

April 20, 2014

Posted by **Hanu** on Monday, March 19, 2012 at 9:56pm.

[4x^1/3]^1/2 [9x]^-3/2 / [27x]^-1/3

- Math -
**Reiny**, Tuesday, March 20, 2012 at 12:19am= 2(x^(1/6) ((1/27) x^(-3/2) (3) (x^(1/3)

= (6/27) x^(1/6-3/2+1/3)

= (2/9) x^-1

= 2/(9x)

**Related Questions**

Math - simplify using the exponent law. express your answer using positive ...

Math - I am to express the following using a positive exponent. Then I have to ...

Please check answers) - Perform the indicated operations and simplify the result...

algebra - write the following using a positive exponent, simplify the expression...

math - How do u simplify . Express final answer using positive exponents. 2^3= (...

math - express using a positive exponent: c^-5

math - I am trying to find the answer to a scientific notation problem, express ...

math - Express y=[4x-x^3]/[3x^2+2)^2 as a product and then differentiate. ...

Math - Simplify the expression using order of operations. 7(9+7)+4(4-1) over 4(6...

calculus - derivatives differentiate y=x^7/3 So far I have Y=7/3X Is this all ...